Aquaculture development : - Pillay, T.V.R. (Fishing news books, 1994)
Aquaculture is the commercial farming of aquatic food products. Provides a critical appraisal of the experiences of the last three decades in order to formulate and implement plans and strategies for the future. An international review of the industry's development is discussed. Includes such topics as planning, production, marketing, risks, insurance, environmental concerns, integrated farming and polyculture.